International Perspectives about COVID-19, Digital Labour and Gender Work Pattern: A Collective Interview - Annette von Alemann; Julia Gruhlich; Ilona Horwath; Lena Weber (Gender a Výzkum)
In this special issue, we want to capture different country perspectives on the connection between the digitalisation of work and gender relations. As a result of the COVID-19 pandemic, the world has suddenly found itself in an exceptional situation that had not been foreseen in our editorial project but proved to be relevant for gendered work patterns and digitalisation. Digital systems and devices have seemed to offer the best solutions to the situation of the pandemic and the subsequent lockdowns all over the world. It has become apparent, however, that not everyone has equal access to the internet and technical knowledge of computing, and that women and men have been affected in very different ways by the COVID-19 crisis in their (digital or not) work environments. To find out more about the situation all over the world, we asked some gender researchers and social and technical scientists from South Africa, Canada, the Czech Republic, Great Britain, Belgium, Finland, and Austria a few questions via e-mail about their personal impressions from the COVID-19 pandemic and their own working situation. What we present here is the innovative format of an 'artificial collective interview': the responses have been shortened and compiled, but not reformulated. However, the questions have been modified to give the impression of a face-to-face group interview, though the interaction actually took the form of one-to-one email communication. The answers were collected during the summer period in August-September 2020. The interviewees were chosen because their work focused on gender and digitalisation even before the COVID-19 crisis and/or because they did research, published, or blogged about the events during the pandemic, or because they have been perceived as experts in areas that have changed rapidly.